Efficient carbonaceous sorbent based on the waste sludge of oil extraction industry for purifying wastewater from petroleum products - I V, Starostina; A E, Nikitina; M M, Kosukhin; Yu.L, Starostina (International Journal of Engineering and Technology, 2018)
The opportunity to use the oil extraction industry waste kieselghur sludge as a raw stuff for carbonaceous sorbent for purifying wastewater from petroleum and petroleum products has been researched. It has been demonstrated that the thermal modification of the waste sludge results in oxidation of organic matter and the formation of a carbon layer on the surface of kieselghur (diatomite), as well as the formation of the obtained material’s porous structure. The maximum values of oil-absorption and petroleum-absorption of the carbonaceous sorbent samples, obtained at various temperatures of the initial waste product treatment, have been determined. The highest petroleum saturation (2 g/g) is observed in the first 5 minutes of the sorbent’s contact with the pollutant and is characteristic of the material, obtained at temperature 500°С. The highest oil saturation (3.6 g/g) is shown by the sorbent, obtained at temperature 450°С. This value was achieved after 30 minutes of the sorbent’s contact with oil. The efficiency of clarifying water-oil emulsion with the concentration 1.5 g/dm3 by using carbonaceous sorbents of various thermal pre-history has been determined. The highest degree of emulsion clarification – 91% was achieved at using the sorbent, obtained as a result of the waste sludge modification at temperature 450°С.